2014
DOI: 10.1155/2014/698542
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Fotemustine in High-Grade Gliomas: From Single Agent to Association with Bevacizumab

Abstract: Fotemustine is a third-generation nitrosourea showing efficacy in various types of tumors such as melanoma and glioma. We reviewed the most important studies on fotemustine treatment in glioma patients analyzing its pharmacological profile and its activity and safety. Fotemustine was used as single agent or in association with new targeted drugs such as bevacizumab; fotemustine was used both as first-line chemotherapy before temozolomide era and in refractory-temozolomide patients during temozolomide era. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Currently, there is a lack of standard treatment strategies for elderly GBM patients. Several studies have demonstrated the efficacy of FTM against newly diagnosed or recurrent high-grade gliomas [32][33][34][35]. Previous trials investigating FTM reported an OS of 9-20 months, PFS of 4-9.1 months, PFS-6 of 27-48.5% and DCR of 47.5-62% [18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a lack of standard treatment strategies for elderly GBM patients. Several studies have demonstrated the efficacy of FTM against newly diagnosed or recurrent high-grade gliomas [32][33][34][35]. Previous trials investigating FTM reported an OS of 9-20 months, PFS of 4-9.1 months, PFS-6 of 27-48.5% and DCR of 47.5-62% [18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…This causes high cytotoxicity, induces DNA double-strand break and prevents DNA replication and transcription to finally result in cell apoptosis and necrosis ( 80 ). Nitrosourea chemotherapeutic drugs have myelosuppression and hematological toxicity ( 80 , 81 ). Due to the limited efficacy of chemotherapeutic drugs when applied alone, previous studies that investigated the effects of multiple combination therapies revealed that the resultant efficacy is superior compared with that in chemotherapy alone ( 30 , 80 , 82 ).…”
Section: Nitrosourea-based Chemotherapymentioning
confidence: 99%
“…That implies not the bevacizumab and fotemustine in-effectiveness per se , but lack of breakthrough achievements against a ground of previous studies. A double-agent regimen applied to grade III glioma resulted in PFS of 5 months and median OS of 8.6 months [ 37 ].…”
Section: Application Of Monoclonal Anti-bodiesmentioning
confidence: 99%